Stereoselectivity of sodium borohydride reduction of saturated steroidal ketones utilizing conditions of Luche reduction - Šťastná, Eva; Černý, Ivan; Pouzar, Vladimír; Chodounská, Hana (Steroids, 2010)
A series of keto steroids were reduced with sodium borohydride in the presence of cerium(III) chloride or samarium(III) iodide (Luche reduction). The ratios of axial and equatorial alcohols were determined by HPLC and the results were compared with those obtained by a standard sodium borohydride reduction. The best results were obtained with the 2-keto derivative 1, 7-keto derivatives 5 and 6, and 12-keto derivative 8 where the cerium(III) ion addition resulted in the inversion of the axial/equatorial ratios. The Luche reduction of the 20-keto derivative 11 improved the proportion of the (20S)-alcohol in a mixture of (20S)/(20R) alcohols up to 35% from 5% in a standard sodium borohydride reduction.
Keywords: ketony; Borohydrides; borohydridy; Ketones; stereoizomerie; steroidy; molekulární struktura; oxidace-redukce; Magnetic Resonance Spectroscopy; Oxidation-Reduction; Stereoisomerism; Steroids; magnetická rezonanční spektroskopie; Molecular Structure